Transoral Approach to Parapharyngeal Space Tumours: Preliminary Reports from a Single-Centre Retrospective Analysis - Giovanni Motta; Domenico Testa; Anna Donadio; Filippo Ricciardiello; Michele Cavaliere; Eva Aurora Massimilla; Gaetano Motta (Current Oncology, 2023)
Purpose: The aim of this study is to identify certain parapharyngeal space tumours with specific characteristics that can be treated successfully through an endoscopically assisted transoral approach (EATA). Methods: Nine patients with PPS tumours underwent surgery through an EATA between 2003 and 2021. All patients underwent clinical examination and fibrolaryngoscopy. Preoperative CT and/or MRI was performed on all patients. Results: All the patients were successfully treated through an endoscopically assisted transoral approach. Histological examination revealed five pleomorphic adenomas, two schwannomas, one ectopic thyroid gland and one lipoma. The only long-term sequelae observed was Horner syndrome in the two schwannomas arising from the carotid space. The mean hospitalisation time was 2.6 days, while the mean follow-up time was of 9.7 years. Conclusions: An endoscopically assisted transoral approach (EATA) is a valid technique for treating benign capsulated tumours of the true PPS and some benign capsulated tumours of the superomedial aspect of the carotid space.